SIHIR BUDAYA MASSA DALAM RELASI SOSIAL KAUM MUDA (ISLAM) MODERN - Abdullah Sumrahadi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
The Muslim youth challenge in current time is the improvement of global culture. It is known as pop culture, so they have new icon The youth generatons next!. It will be a dream and they hard struggle to realized it. Because of the problem of youth, this article describe: (1) give knowledge to youth generation about this culture as new culture that will run fast and have high implication in their life and (2) the youth generation should be prevent from the impact of this culture. This prevent is very important because the pop culture to embed their effect trough many ways, mainly power of media